2018
DOI: 10.1016/j.neuropsychologia.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating between the N2pc and attentional shifting: An attentional blink study

Abstract: The N2pc is routinely used as an electrophysiological index of attentional shifting. Its absence is thus taken as evidence that no shift of attention occurred. We provide evidence in contrast to this notion using a variant of the attentional blink (AB) paradigm. Two target letters, embedded in two streams of distractor letters and defined by their color, were separated by either 300 or 800 ms. The second target was preceded by a distractor frame of the same color (cue). As expected, identification of the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 99 publications
2
67
2
1
Order By: Relevance
“…In our experiments, we observed a robust target-evoked N2pc even when we verified with alpha-band activity that observers had precisely attended the target location in advance. This finding is difficult to reconcile with the early view that the N2pc reflects a shift of covert spatial attention to a target stimulus (Eimer, 1996;Woodman and Luck, 1999) but dovetails with other recent evidence that the N2pc can be dissociated from shifts of spatial attention (Zivony et al, 2018). This result can be naturally explained by an individuation account of the N2pc (Mazza and Caramazza, 2015).…”
Section: Implications For the Interpretation Of The N2pc Componentcontrasting
confidence: 75%
See 1 more Smart Citation
“…In our experiments, we observed a robust target-evoked N2pc even when we verified with alpha-band activity that observers had precisely attended the target location in advance. This finding is difficult to reconcile with the early view that the N2pc reflects a shift of covert spatial attention to a target stimulus (Eimer, 1996;Woodman and Luck, 1999) but dovetails with other recent evidence that the N2pc can be dissociated from shifts of spatial attention (Zivony et al, 2018). This result can be naturally explained by an individuation account of the N2pc (Mazza and Caramazza, 2015).…”
Section: Implications For the Interpretation Of The N2pc Componentcontrasting
confidence: 75%
“…This account is closely related to the individuation account because localization is considered a necessary component of object individuation (Kahneman et al, 1992;Xu and Chun, 2009). Zivony et al (2018) proposed another possibility. Specifically, Zivony et al suggested that the N2pc reflects attentional engagement, which they distinguished from the deployment of spatial attention.…”
Section: Implications For the Interpretation Of The N2pc Componentmentioning
confidence: 99%
“…Accordingly, the N2pc seems to reflect processes akin to what we referred to as attentional engagement in the section titled Processing stages in a typical PoP experiment (see Zivony, Allon, Luria & Lamy, 2018 for related evidence).…”
Section: Pop and Event-related Potentialsmentioning
confidence: 92%
“…Finally, PAF suggests a more parsimonious account of the extant findings, as it does not require a distinction between attentional shifts and attentional engagement. In keeping with the core insight of the camera model (Zivony, Allon, Luria & Lamy, 2018;Zivony & Lamy, 2016), PAF also posits that cue validity and compatibility effects can be dissociated and are not two equivalent measures of attentional selection as is often assumed (e.g., Theeuwes et al, 2000). However, according to PAF, these measures do not reflect attentional shifting and engagement, respectively.…”
Section: Relation To Other Models Of Attentionmentioning
confidence: 96%